A theory for the free vibration of a laminated composite rectangular plate with holes in aerospace applications. (1st November 2020) - Kim, Yongha; Park, Jungsun
Abstract: This article defines the effective stiffness of a laminated composite rectangular plate with holes by the homogenization method. Based on the continuous model, a theory is presented for conducting a free vibration analysis of the laminated composite rectangular plate with holes. The theory is derived by the Ritz method. The validity of the theory is verified by comparing the results of the finite element analysis (static/modal analyses). Finally, we investigate the effects of the design parameters on the vibration characteristics of the laminated composite rectangular plates with holes by a parametric analysis based on the present method. The results allow a database to be obtained on the structural characteristics of laminated composite rectangular plates for applying aerospace applications. Consequently, it is concluded that the theory is well suited to free vibration analysis of a laminated composite rectangular plate with holes for aerospace applications due to their relative simplicity and computational efficiency.